Technological, Pedagogical, and Content Knowledge (TPACK) untuk Penguasaan Konsep dan Kemandirian Belajar Bahasa Indonesia Siswa - Mardhiati, Ayinun (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The Covid-19 pandemic has had an extraordinary impact on various fields, including education. The pattern of learning that has been carried out face-to-face must change to virtual or distance learning. Learning patterns like this actually cause learning loss in students. In addition, the emergence of learning achievement gaps caused by differences in access and quality of learning. This problem can be overcome by applying a Technological, Pedagogical, and Content Knowledge (TPACK) approach in learning. This study aims to describe the application of the TPACK approach in improving students' mastery of concepts and self-reliance in learning Indonesian in a blended learning manner at SMP Negeri 32 Makassar. This research is a qualitative descriptive research. The source of this research data is the process of implementing Indonesian language learning and mastery of concepts and student learning independence. The research subjects were class VIII students. The results of the study show that the use of the TPACK approach applied in learning Indonesian at SMP Negeri 32 Makassar can improve students' mastery of concepts and independent learning. In addition, understanding the concept of knowledge of technology, pedagogy, and content in blended learning in schools is a form of learning that represents the Freedom to Learn program.